PENDIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Siti Suwaibatul Aslamiyah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
Educationis amajor factor inthe success ofeducation. Its presencein the learning processis very importantandcan not bereplaced bythe mostmoderntechnologythough,becauseonly througheducator/teacherhumanelementssuchidealscan be achieved.In an articleentitled